On the Necessity of Prevalence Studies on Circumscribed Choroidal Hemangioma in Iraq - Al-Imam, Ahmed M.; Al-Zahawi, Farah A.; Sahai, Ashok (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Circumscribed choroidal hemangioma (CCH), a rare benign tumor, poses significant risks to vision due to its proximity to the macula, with epidemiology varying from one population to another.Objectives: The present article emphasizes the need for prevalence studies on CCH in Iraq.Methods: In June 2023, a literature review was conducted on PubMed, followed by a secondary analysis of patients' demographic data from diverse populations and ethnic groups worldwide.Results: The secondary literature analysis revealed demographic variations in CCH, including age and gender (male-to-female) ratios, and across different populations. The exact prevalence remains unclear, particularly in Iraq, due to limited data and asymptomatic cases. Accurate diagnosis through imaging techniques is crucial for symptomatic cases, with treatment modalities like PDT available. Economic challenges persist in Iraq, highlighting the need for collaboration between healthcare and government sectors. Conclusion: The lack of CCH prevalence studies in Iraq impedes understanding and management, impacting ophthalmology care for Iraqi patients. Addressing this gap through research can benefit local healthcare authorities and provide essential data for the Middle East and other regions worldwide